2013
DOI: 10.1016/j.msea.2013.05.068
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deformation temperature on niobium clustering, precipitation and austenite recrystallisation in a Nb–Ti microalloyed steel

Abstract: The effect of deformation temperature on Nb solute clustering, precipitation and the kinetics of austenite recrystallisation were studied in a steel containing 0.081C-0.021Ti-0.064 Nb (wt%). Thermo-mechanical processing was carried out using a Gleeble 3500 simulator. The austenite microstructure was studied using a combination of optical microscopy, transmission electron microscopy, and atom probe microscopy, enabling a careful characterisation of grain size, as well as Nb-rich clustering and precipitation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…study is consistent with the austenite grain structure development in the studied steel presented by us in an earlier work. [27] After deformation at 1348 K (1075°C), the austenite grain structure was fully recrystallized, deformation at 1248 K (975°C) resulted in partial recrystallization, and deformation at 1098 K (825°C) led to the formation of pan-caked microstructure with elongated non-recrystallized austenitic grains. A larger amount of crystal defects (shear bands, sub-grain boundaries, and dislocations) inherent in lower temperature austenitic microstructures resulted in (1) an increased number of the ferrite nucleation sites during phase transformation and (2) the ferrite grain refinement.…”
Section: A Effect Of Tmp On Microstructurementioning
confidence: 99%
“…study is consistent with the austenite grain structure development in the studied steel presented by us in an earlier work. [27] After deformation at 1348 K (1075°C), the austenite grain structure was fully recrystallized, deformation at 1248 K (975°C) resulted in partial recrystallization, and deformation at 1098 K (825°C) led to the formation of pan-caked microstructure with elongated non-recrystallized austenitic grains. A larger amount of crystal defects (shear bands, sub-grain boundaries, and dislocations) inherent in lower temperature austenitic microstructures resulted in (1) an increased number of the ferrite nucleation sites during phase transformation and (2) the ferrite grain refinement.…”
Section: A Effect Of Tmp On Microstructurementioning
confidence: 99%
“…The enrichment of C on the prior-austenite grain boundaries was directly observed using atom probe microscopy [208,209]. A study by Kostryzhev et al [209] is shown in Figure 5-12 as an example.…”
Section: Influence Of C On Austenite Grain Growth Behaviourmentioning
confidence: 99%
“…Furthermore, APT can also measure the chemical composition of the matrix excluding even the smallest precipitates or clusters into the composition calculation [32], contrary to other spectroscopy techniques. APT was used to characterize (Nb,Ti)(C,N) particles formed during hot-rolling [33][34][35][36][37]. Nöhrer et al investigated the influence of deformation level [33] while Kostryzhev and Pereloma et al investigated the influence of the deformation temperature [34,35] on the precipitation of (Nb,Ti)(C,N) in low-alloyed steels.…”
Section: Introductionmentioning
confidence: 99%